Implementation of Beginning Reading Activities at Bebandem State Kindergarten, Karangasem Regency, Bali Province - Ni Luh Juli Erlianti; Muthmainah Muthmainah (International Journal of Educational Research, 2025)
This study aims to describe the implementation of early reading activities at Bebandem State Kindergarten, Karangasem Regency, Bali District for Group B, children aged 5-6 years. The focus of this research is on the planning, implementation, evaluation, supporting factors, and inhibiting factors of early reading activities. This study employs a qualitative approach and descriptive research type. Data collection techniques include interviews, observations, and documentation. Data are analyzed qualitatively using the Miles and Huberman model, which involves data collection, data condensation, data presentation, and conclusion drawing. The validity of the research data was re-evaluated using source triangulation and method triangulation. The results show that: 1) The planning of early reading learning activities at Bebandem State Kindergarten begins with a socialization activity through In-House Training (IHT), building a shared commitment where teachers are invited to prepare a lesson plan or teaching module that meets the needs of the students. 2) The implementation of learning uses picture and letter card games, where children are invited to play cards according to the current theme; 3) The evaluation of early reading activities at Bebandem State Kindergarten is conducted through observation, assessing the implementation of learning activities, and identifying actions to improve any shortcomings in the learning activities carried out. 4) The supporting factors of early reading learning activities at Bebandem State Kindergarten include guidance from parents and families in early reading activities. 5) The inhibiting factors in the implementation of learning include both internal and external factors. Internal factors include intelligence, interest, talent, and motivation, while external factors include family environment, school environment, and community environment.